Factors Determining Non-Performing Financing In Islamic Banks In Indonesia - Nurulloh, Maulana Syarif; Indriawati, Fitri (Economics & Islamic Finance Journal (ECIF), 2024)
This study aimed to determine the factors that impact non performing financing at Shariah Bank in Indonesia (Empirical study based on Shariah Bank listed on Indonesia financial services authority for the period 2017- 2020). This study is using purposive sampling as sampling method, which is sampling technique using several consideration according to the used criteria to determine how much sample to be studied and the final results obtained 44 samples. The type of this study is quantitative and the data that used for this study is secondary data. This study uses multiple regression analysis as a testing tool. The result of this study indicate capital adequacy ratio and shariah board committee shows a negative effect on non performing financing, operational efficiency ratio (BOPO) shows a positive effect on non performing financing. Meanwhile BI Rate, inflation, and independent commissioner had no effect on non performing financing.